Gestionar la frustración: experiencias relacionales de antropólogas forenses en el contexto del conflicto armado colombiano - Juan Pablo Aranguren Romero; Gabriela Fernández Miranda (Nuevo mundo - Mundos Nuevos, 2021)
This paper analyzes how three Colombian forensic anthropologists manage labor frustration and what motivates them to carry on working despite the high probability of not succeeding. This analysis inquiries about the role of the commitment with the victim’s families in relation to the motivation needed to maintain the efforts in searching, exhuming, identifying and returning the body remains of forced disappearance victims in the context of politic violence and war in Colombia. Considering the cases that have not been successful, this article examines the emotional management that forensic anthropologists build with the victim’s families, and the intersubjective relationship between them. It’s shown that in not successful cases, the forensic anthropologists experiences have involved attending to the family’s expectations, facing the institutional terms and conditions and the security problems in ground, and creating strategies to manage the frustration of not achieving their goals.